Strategies for upgrading the training of personnel at the Shanghai Municipal and district Centers for Disease Control and Prevention - HE Yongchao; SUI Mengyun; LI Yugang (Shanghai yufang yixue)
ObjectiveTo investigate the current status of personnel training, barriers and bottlenecks at Shanghai Municipal and district Centers for Disease Control and Prevention (hereinafter referred to as" CDC"), so as to provide a reference basis for the formulation of training policies that are consistent with the CDC’s staff development path, characteristics of the era, and features of Shanghai mega⁃city.MethodsQuestionnaire survey and qualitative interview were used to collect the data, covering the basic information of the research subjects, as well as training status, needs, barriers and problems. A total of 800 questionnaires were distributed, and 768 valid questionnaires were returned, and frequency counts and composition ratios were used for statistical description.ResultsAmong the research subjects, 568 of which were females, accounting for 73.96%, with an average age of 36.51 years. Almost 93.10% of the research subjects had participated in training in the last year, while 6.90% of whom hadn’t attended any kind of training ever, with the main reasons as follows: failure to receive notification of training, unavailability of work, lack of funding, limited number of places and unsuitable content. Furthermore, 12.63% of the research subjects thought the trainings provided could not satisfy the requirements for continuing medical education credits, and the top three common forms of training were lectures/conferences, training courses with credits, and online courses. 97.27% of the research subjects had a need for training, and 56.12% of which expected to train for 2‒3 days, and the ideal number of training sessions per year was 2‒3 and 4‒5 times. All the staff, whether they were from the municipal CDC or district CDC, preferred practical training and case lectures to theoretical lectures. However, staff from municipal CDC had a higher demand for official document writing and research project design, and staff from district CDC had a higher demand for data software analysis and thesis writing. Bottlenecks mainly included some training needs incapable of being satisfied currently, single form of training that didn’t take advantage of the support of digital technology and lacked flexibility and convenience, and a lack of channels and mechanisms for the dissemination and transmission of training information.ConclusionStrategies to improve the training of CDC personnel at both the district and municipal levels include the creation of a hierarchical and progressive training model and system for different populations, an extension of training forms, containing the establishment of a unified training platform and the creation of an online knowledge base; and the construction of a unified and open platform with a smooth release and transfer mechanism for the dissemination of training information.